Pengaruh Pengungkapan Sustainability Report Terhadap Nilai Perusahaan Yang Tergabung Dalam LQ 45 Tahun 2012-2013 - Apri Dwi Astuti; Juwenah Juwenah (UNSIKA (Universitas Singaperbangsa Karawang), 2017)
The purpose of this study was to examine and analyze sustainability report effectively to the firms value of LQ 45. Sustainability report was reflected by Economic performance, social performance and enviromental performance with indicator for GRI G3 by 79 items. Dependent variabel was reflected by the firm value with stock price. The sample was determined by using purposive sampling. population of this study is firms which has stock high performance in the stock market. This study used 30 firms as a sample is consistently listed on LQ 45 in Indonesia Stock Exchange during 2012-2013. Analysis of data in this study used SPSS. The result showed that economic performance of sustainability report had effect on firm value, social performance of sustainability report have not effect on firm value and enviromental performance same too.